2017
DOI: 10.1159/000479802
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Potassium with All-Cause Mortality in Patients with and without Heart Failure, Chronic Kidney Disease, and/or Diabetes

Abstract: and highest in the combined cohort 29.7%. Higher mortality rates were noted in those aged ≥ 65 vs. 50-64 years. In an adjusted model, all-cause mortality was significantly elevated for every 0.1 mEq/L change in potassium <4.0 mEq/L and ≥ 5.0 mEq/L. Diuretics and renin-angiotensin-aldosterone system inhibitors were related to hypokalemia and hyperkalemia respectively. Conclusion: Mortality risk progressively increased with dyskalemia and was differentially greater in those with HF, CKD, or DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
233
2
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(270 citation statements)
references
References 23 publications
(26 reference statements)
11
233
2
14
Order By: Relevance
“…2 Adjusted IRRs estimated in our study illustrated the association between serum potassium concentrations outside 4.0-5.0 mmol/L and an increased risk of mortality among incident HF patients. This may imply that our results are more generalizable to other countries and health care systems, compared with those founded on relatively short-term, claims-based data sets.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…2 Adjusted IRRs estimated in our study illustrated the association between serum potassium concentrations outside 4.0-5.0 mmol/L and an increased risk of mortality among incident HF patients. This may imply that our results are more generalizable to other countries and health care systems, compared with those founded on relatively short-term, claims-based data sets.…”
mentioning
confidence: 51%
“…[8][9][10] At present, the clinical burden of hypokalaemia and hyperkalaemia among European HF patients, and relationships between serum potassium and adverse clinical outcomes in this population, is not well characterized. 2 Using primary care data obtained from the Clinical Practice Research Datalink (CPRD), 15,16 this study developed risk equations to describe associations between serum potassium and the incidence of death, major adverse cardiac events (MACE), and RAASi discontinuation, in a UK cohort of newly diagnosed HF patients. 2 Using primary care data obtained from the Clinical Practice Research Datalink (CPRD), 15,16 this study developed risk equations to describe associations between serum potassium and the incidence of death, major adverse cardiac events (MACE), and RAASi discontinuation, in a UK cohort of newly diagnosed HF patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collins et al[8] have recently demonstrated in a nationwide electronic medical record ( n = 1,716,141 with ≥2 potassium values) that the presence of HF appears to considerably elevate the fatal risks of hyperkalemia in patients treated with RAAS inhibitors. They found that all-cause mortality was 25.7% at potassium values of 4.0–<5.0 mEq/L and 45.5% at >5.0 mEq/L.…”
mentioning
confidence: 99%
“…This study by Thomsen et al confirms previous smaller studies and hospital-based data identifying the same people at risk for hyperkalaemia. Moreover, a recent analysis of data on >900 000 people from a different database suggests that hyperkalaemia should be redefined among those with chronic kidney disease and diabetes and especially those with chronic kidney disease, heart failure and diabetes [10]. In that analysis, cardiovascular mortality was significantly higher when serum potassium level was >5 mmol/l, with a relative risk of 4.09 among those stage 3b chronic kidney disease, whereas diabetes alone without chronic kidney disease had a much lower relative risk, albeit elevated [10].…”
mentioning
confidence: 99%